EL DIÁLOGO INTERTEXTUAL EN PROPERCIO 4.9 - Schniebs, Alicia (Myrtia, 2003)
In this paper we analyze Propertius’ elegy 4.9 starting from the dialogue that this text establishes with other literary texts and with the Hellenistic-Augustan metatext. We postulate that the poet through a procedure of deconstruction and construction presents a Callimachean-Propertian Hercules who acknowledges the aesthetic principles stated in the first programmatic poem of the collection.